Career Management in Building Teacher Professional Performance - Yanti Hasbian Setiawati; Hasan Baharun; Halimatus Sa'diyah; Yuni Hidayati (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Teacher professionalism plays an essential role in educational institutions. Therefore, appropriate management is needed to realize the teacher's professional performance as expected. This study aims to analyze career management in building the teacher's professional performance in early childhood education institutions. The research method used is a qualitative case study type. Case study qualitative research was chosen to answer and explain the phenomenon of career management that has been carried out by finding more appropriate ways today. Data was obtained using observation, interviews and documentation. Data analysis techniques are data collection, data reduction, data presentation and conclusion. The study results show that there are four points carried out by institutions in building teacher professional performance, including; Internal and external analysis, strengthening work commitment, good competence, and continuous evaluation. Career management is the main ingredient that needs to be developed by educational institutions in fostering a professional attitude towards their performance so that the desired goals can be realized optimally.